Isolation, Purification and Identification of the Anti-Diabetic Components from Cinnamomum zeylanicum and Cinnamomum cassia Bark Oil Extracts - and R. Murugesan2, S. Elumalai1*, R. Kesavan1, S. Ramganesh (Current Botany, 2011)
The bark and the leaves Cinnamomum sp are commonly used as spices in home kitchens and their distilled essential oils are used as flavouring agent in the food & beverage industries. The chemical analysis of the oils from both the sources revealed that the active oil contained 74% cinnamaldehyde, compared to only 8.3% in the inactive oil. Cinnamon has been reported to have remarkable pharmacological effects in the treatment of type II diabetes and insulin resistance. However the plant material used in the study was mostly from C. cassia and only few of them are truly from C. zeylanicum. Three types of distinguishing method for cinnamon barks have been described: Microscopy, Mucilage content determination and Thin layer chromatography (TLC). The preparatory TLC fractionation of ether, extracted from C.cassia and C. zeylanicum yielded 3 fraction representing 58.5% of the crude extract. Similar to the ether extract the preparative TLC of the distilled oil also yielded 3 fraction with a combined yield of 97.5% of the crude distilled oil. The Gas Chromatography/Mass spectrophotometry (GS/MS) of the fraction 2 of ether extract, yielded 4 peaks, with the relative intensity of 4, 6, 61,6 and 29%. The first and second most intense peaks were identified as cinnamaldehyde and cinnamic acid repectively. The remaining two peaks with relative intensity of 6% or less could not be identified. The GC/MS of the fraction 2 of the distilled oil yielded only one peak with the relative intensity of 99.1% which was identified as cinnamaldehyde.